(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To develop a nursing protocol to guide perioperative care for individuals with intestinal ostomies. Method: A methodological study conducted between March and June 2022, using a quantitative approach. The study was divided into three stages: 1) an exploratory phase to determine the characteristics of the target population using a questionnaire; 2) the definition of perioperative recommendations based on Enhanced Recovery After Surgery® (ERAS); and 3) the creation of the protocol. Data analysis involved simple descriptive statistics. Results: Ten (10) patients responded preoperatively, while only six (6) responded postoperatively. Preoperative education was provided by nurses in 50% of cases. Findings showed an absence of ostomy site marking in 90% of cases, insufficient self-care in 60%, and postoperative complications in 60%, including edema, mucocutaneous separation, contact dermatitis, peristomal hernia, edge maceration, and granuloma. The proposed protocol consists of a care flowchart with four lines of follow-up within the institution and a consolidated framework with four key axes of perioperative nursing actions. Each axis includes sub-axes that detail specific guidelines to be implemented. Conclusion: The situational analysis of the target population and perioperative complications demonstrated the feasibility of developing a perioperative care protocol focused on the immediate preoperative, intraoperative, and postoperative phases.